Testosterone Contributes to Vascular Dysfunction in Young Mice Fed a High Fat Diet by Promoting Nuclear Factor E2–Related Factor 2 Downregulation and Oxidative Stress - Costa, Rafael M.; Alves-Lopes, Rhéure; Alves, Juliano V.; Servian, Carolina P.; Mestriner, Fabíola L.; Carneiro, Fernando S.; Lobato, Núbia de S.; Tostes, Rita C. (Frontiers in Physiology, 2022)
Obesity, an important risk factor for cardiovascular disease, promotes vascular oxidative stress. Considering that free testosterone levels remain within the reference range, especially in obese young men and that testosterone stimulates reactive oxygen species (ROS) generation, we sought to investigate whether testosterone interferes with obesity-associated oxidative stress and vascular dysfunction in male mice. We hypothesized that testosterone favors ROS accumulation and vascular dysfunction in high fat diet (HFD)-fed obese mice. We also questioned whether testosterone downregulates the nuclear factor E2–related factor 2 (Nrf2), one of the major cellular defense mechanisms against oxidative stimuli. Male C57Bl/6J mice were submitted to orchiectomy or sham-operation. Mice received either a control diet (CD) or HFD for 18 weeks. Vascular function was assessed in thoracic aortic rings and molecular mechanisms by which testosterone contributes to vascular dysfunction were determined. HFD reduced acetylcholine-induced vasodilation and increased vascular ROS generation in sham mice. Castration prevented these effects. Treatment of castrated mice fed either the CD or HFD with testosterone propionate decreased acetylcholine vasodilation. HFD decreased Nrf2 nuclear accumulation, events linked to decreased mRNA expression and activity of Nrf2-regulated enzymes (catalase, heme oxygenase-1, peroxiredoxin and thioredoxin). These events were prevented in HFD-fed castrated mice. Bardoxolone, a Nrf2 activator, increased nuclear accumulation of Nrf2, decreased ROS generation and improved acetylcholine vasodilation in HFD-fed sham mice. In vitro, testosterone increased ROS generation and decreased Nrf2 nuclear accumulation. These effects were prevented in the presence of an androgen receptor antagonist, an inhibitor of gene transcription and an inhibitor of the pro-oxidant enzyme NOX-1 These results indicate that testosterone downregulates Nrf2, leading to oxidative stress and vascular dysfunction in HFD-fed obese mice.